Investigating EFL Teachers’ Knowledge and Practice in Vocabulary Instruction - Bekele Daba Shube; Alemu Hailu (English Department of Faculty of Tarbiyah and Teacher Training, 2022)
The purpose of this study was to investigate EFL teachers’ knowledge and practice in vocabulary instruction. The study involved thirty six secondary school English teachers from three randomly selected schools. Simple random, purposive and available sampling techniques were employed for the study undertaken. Data was collected from the participant teachers through questionnaire, semi-structured interview, classroom observation and stimulated-recall interview. The findings show that, teachers’ knowledge was generally consistent with their classroom practices and this marked their knowledge guides their pedagogical practices. However, a few inconsistencies were also noticed. At the same time, the finding exhibited factors which could contribute to the mismatches between teachers’ knowledge and practices in vocabulary instruction. These factors include: Students’ lack of ability, their lack of motivation, lack of resources, large class size and others. The discussion of these findings suggests implications for practices and recommendations for future research to improve vocabulary instruction in secondary school context.